Semiotics Analysis of Racism in the Comic Captain America: Sam Wilson - Junior, Maldini Radjab; Juanda (TALENTA Publisher, 2022)
Racism is still common, especially against African Americans in the United States and is a problem that until now has not been resolved. Racism is again a hot topic as police brutality started popular movements such as Black Lives Matter that tried to raise awareness about racism in the United States. The comic